The case of the case of mistaken identity - Barnett, Mac (Barnett, Mac. Brixton brothers, 2009)
When twelve-year-old Steve Brixton, a fan of Bailey Brothers detective novels, is mistaken for a real detective, he must elude librarians, police, and the mysterious Mr. E as he seeks a missing quilt containing coded information.